2021
DOI: 10.1029/2020wr028519
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors Controlling the Error Characteristics of the Surface Water and Ocean Topography Mission Discharge Estimates

Abstract: The Surface Water and Ocean Topography (SWOT) satellite mission will measure river width, water surface elevation, and slope for rivers wider than 50-100 m. SWOT observations will enable estimation of river discharge by using simple flow laws such as the Manning-Strickler equation, complementing in situ streamgages. Several discharge inversion algorithms designed to compute unobserved flow law parameters (e.g., friction coefficient and bathymetry) have been proposed, but to date, a systematic assessment of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 61 publications
(133 reference statements)
4
61
0
Order By: Relevance
“…Intermittent satellite-based discharge estimates can be derived from optical and altimeter data (Abdalla et al, 2021;Tarpanelli et al, 2021). The Surface Water and Ocean Topography (SWOT) mission will soon enable frequent spaceborne observations of river stage for large rivers to allow inference of discharge (Biancamaria et al, 2016;Frasson et al, 2021). Currently, no mission is specifically dedicated to ET measurements (Fisher et al, 2017), and ET is most typically inferred from satellite-observed surface or skin temperature (related to sensible heat) as the residual of a simple energy balance model (Anderson et al, 2021), or indirectly obtained via soil moisture and VOD DA in a land surface model (Martens et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…Intermittent satellite-based discharge estimates can be derived from optical and altimeter data (Abdalla et al, 2021;Tarpanelli et al, 2021). The Surface Water and Ocean Topography (SWOT) mission will soon enable frequent spaceborne observations of river stage for large rivers to allow inference of discharge (Biancamaria et al, 2016;Frasson et al, 2021). Currently, no mission is specifically dedicated to ET measurements (Fisher et al, 2017), and ET is most typically inferred from satellite-observed surface or skin temperature (related to sensible heat) as the residual of a simple energy balance model (Anderson et al, 2021), or indirectly obtained via soil moisture and VOD DA in a land surface model (Martens et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…16 of these rivers are then additionally validated under a "measurement-error" scenario that more closely mimics expected SWOT by adding realistic radar errors and sampling along the satellite's future ground track. SWOT river error modeling was developed by Durand et al (2020) and then applied to these 16 rivers by Frasson et al (2021). This error modeling is non-trivial and computationally expensive, and so…”
Section: Datamentioning
confidence: 99%
“…(2019) (https://doi.org/10.1029/2019GL084529), Frasson et al. (2021) (https://zenodo.org/record/3817817), Churchill et al. (1964) (https://pubs.usgs.gov/pp/0737/report.pdf), Owens et al.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 2 more Smart Citations